2009
DOI: 10.1007/s12130-009-9070-3
|View full text |Cite
|
Sign up to set email alerts
|

Designing Mobile Systems in Highly Dynamic Scenarios: The WORKPAD Methodology

Abstract: The design of interactive systems to be used in mobile and pervasive scenarios, such as emergency management, requires novel methodologies which combine user-centred design approaches and software engineering approaches tailored for distributed architectures. In this paper, the methodology adopted in a successful research project is presented together with a case study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…As far as we know there is no development certification for mobile applications, for which reason the proposed development process for mobile applications was put together from different sources [4] [20] [21] [22].…”
Section: Process Organizationmentioning
confidence: 99%
“…As far as we know there is no development certification for mobile applications, for which reason the proposed development process for mobile applications was put together from different sources [4] [20] [21] [22].…”
Section: Process Organizationmentioning
confidence: 99%
“…Based on the understanding of how Civil Protection works in Italy and other countries stemming from the collected user requirements (de Leoni et al 2007;Humayoun et al 2009), WORKPAD identified two user typologies, backend and front-end users. Front-end users are the operators acting directly in the field during emergency management, whereas back-end users are those who manage the situation from control rooms, providing instructions and information to front-end operators.…”
Section: The Workpad Architecturementioning
confidence: 99%
“…By this we mean functionality supporting planning and accomplishing of the tasks and actions performed by the emergency response personnel (Humayoun et al, 2009). Having plans and tasks explicit in the operations close to the scene of the incident is not so common in our findings, but in the cases where plans and tasks are managed by a higher level of operation, having access to this information is important, including receiving tasks and reporting progress/fulfilment of the tasks.…”
Section: Actions and Plansmentioning
confidence: 99%